Digital Literacy and Academic Writing in the Age of AI:: Evidence from Undergraduate Students - Salsabila, Syarifah; Lengkanawati, Nenden Sri (International Journal of Language Teaching and Education, 2026)
In today’s AI-mediated educational landscape, digital literacy is a crucial skill for language learners and educators. This study investigates the relationship between digital literacy competence and academic writing performance among EFL undergraduate students. Employing a sequential explanatory mixed-method design, the study involved 68 sixth and eighth-semester students who had completed ICT and academic writing courses. Data were collected through a Digital Literacy Scale (DLS) questionnaire, an online academic writing test monitored using AI-based auto-proctoring tools, and follow-up interviews. Results showed that while most participants demonstrated high digital literacy, there was no statistically significant correlation between composite digital literacy scores and academic writing performance. However, dimension-level analysis revealed that three of nine dimensions, Critical Thinking, Character, and Citizenship, yielded weak but significant positive correlations with writing performance (rs = .247, .246, and .269 respectively, p < .05), suggesting that academically proximate competencies, rather than digital literacy as a whole, warrant targeted attention. Interviews revealed students perceived digital tools as useful for access and formatting, but not as direct enhancers of writing quality. These findings highlight a disconnect between general digital fluency and academic writing competence, suggesting technology integration should move beyond access and convenience toward fostering the evaluative and ethical digital competencies most relevant to academic writing. This study contributes to discussions on optimizing digital and AI tools in EFL writing instruction, proposing a more dimension-sensitive approach to digital literacy integration in EFL curricula.